2007
DOI: 10.1016/j.mito.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial drug delivery and mitochondrial disease therapy – An approach to liposome-based delivery targeted to mitochondria

Abstract: Recent progress in genetics and molecular biology has provided useful information regarding the molecular mechanisms associated with the mitochondrial diseases. Genetic approaches were initiated in the late 1980s to clarify the gene responsible for various mitochondrial diseases, and information concerning genetic mutations is currently used in the diagnosis of mitochondrial diseases. Moreover, it was also revealed that mitochondria play a central role in apoptosis, or programmed cell death, which is closely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 62 publications
0
67
0
Order By: Relevance
“…Liposomebased carriers can import hybrid molecules into mitochondria of whole cells, but this approach suffers from low efficiency and high cytotoxicity (8,25,39). Mutated mtDNA can be removed from the germ line by transfer of the spindle-chromosomal complex from one egg to another that is enucleated and depleted of its mitochondria (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomebased carriers can import hybrid molecules into mitochondria of whole cells, but this approach suffers from low efficiency and high cytotoxicity (8,25,39). Mutated mtDNA can be removed from the germ line by transfer of the spindle-chromosomal complex from one egg to another that is enucleated and depleted of its mitochondria (40).…”
Section: Discussionmentioning
confidence: 99%
“…Still, there is some recent evidence for recombination between mtDNA molecules (22), which could enable gene replacement. Although a natural DNA mitochondrial import has been reported in isolated rat liver mitochondria (23) and in plants (24), exogenous DNA cannot be transfected into mitochondria by conventional techniques (25,26). Therefore, the most important challenge at present is the development of procedures for introducing DNA into mitochondria, ideally in intact cells or living tissues.…”
mentioning
confidence: 99%
“…Mitochondrial dysfunction is implicated in a variety of human diseases, including mitochondrial inherited diseases, neurodegenerative disorders, diabetes mellitus and cancer (Chan, 2006;Reeve et al, 2008;Schapira, 2006;Wallace, 2005), therefore, mitochondria would be expected to be the target organelle for these diseases (Armstrong, 2007;Du and Yan, 2010;Fulda et al, 2010;Giorgi et al, 2012;Gogvadze et al, 2009;Yamada et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years a number of outstanding review articles have been published that discussed various ways to bring drugs or chemicals into mitochondria [2][3][4][5][6]. This review.article will summarize various unique features of mitochondria and then review how others suggested that those might be exploited to permit compounds to enter it.…”
Section: Introductionmentioning
confidence: 99%